PENGARUH PENGGUNAAN MOOCs TERHADAP HASIL BELAJAR PPKn SISWA SMP - Harsuani; Nurhikmah H; Farida Febriati (Jurnal Muara Pendidikan, 2025)
The primary focus of this study is on the challenges faced by some students in understanding the material through online learning systems. These difficulties arise because the material presented is considered unengaging, thus hindering the achievement of the expected learning objectives. This research aims to describe the implementation of MOOCs (Massive Open Online Courses) in Civics Education (PPKn) and assess the impact of using MOOCs on the learning outcomes of eighth-grade students at SMPN 6 Makassar. The approach used in this study is a quantitative method with a pre-experimental design. The sample selection was carried out using Purposive Sampling, involving 40 students chosen based on the results of observations and interviews with teachers, which indicated that the characteristics of the students in the class varied significantly, particularly in terms of their abilities and access to learning materials. The findings from the implementation of MOOCs show that both students and teachers feel that MOOCs support the achievement of learning goals and provide a more engaging learning experience. Data analysis using the Wilcoxon Signed Rank Test revealed a significant improvement in student learning outcomes after the implementation of MOOCs, with a significance value of 0.000 (p < 0.05). These findings suggest that the implementation of MOOCs has a significant positive impact on the improvement of student learning outcomes in Civics Education (PPKn) at SMPN 6 Makassar for eighth-grade students.